2008
DOI: 10.1007/s11269-008-9312-2
|View full text |Cite
|
Sign up to set email alerts
|

Water Productivity in a Rigid Irrigation Delivery System

Abstract: The rotational irrigation water delivery (warabandi) system practiced in the Indus river basin of Pakistan has continued for 100 years. Irrigation water allocated to the farmers under the warabandi system is proportional to farm size and is fixed. This rigid allocation system has been partly justified by its contribution to social equity though this may have been at the cost of economic gains. In order to assess the operation of warabandi's basic rules, a farmers' survey was completed from 124 farmers located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Performance evaluation of the irrigation scheme has been carried out for different purposes, such as performing diagnostic analysis [5,6], understanding irrigation behavior and general irrigation trends [7], and comparing the performance of one irrigation scheme with another [8,9]. Evaluation indicators can be categorized into two main groups: external and internal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Performance evaluation of the irrigation scheme has been carried out for different purposes, such as performing diagnostic analysis [5,6], understanding irrigation behavior and general irrigation trends [7], and comparing the performance of one irrigation scheme with another [8,9]. Evaluation indicators can be categorized into two main groups: external and internal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in Pakistan revealed that scarce irrigation water was being allocated to inefficient farmers under the warabandi 1 system, where value of a single unit of water was found very low [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The farmers, with the assistance of irrigation officials have rearranged the irrigation water delivery system (warabandi) rules. The influential farmers have set their own rules to get extra water for meeting the crop-water demand of their farms [2,3]. These practiced rules favor the owners of the larger farms and those whose farms are at the upstream ends of the distributary watercourses [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the farmers have almost no control over the amount or timing of their water deliveries they have little or no incentive to make efforts to improve productivity. Any efforts they make can be negated by the unreliability of supplies (Zardari and Cordery, 2009). As stated above, obstacles to initiative on the part of farmers are common in many irrigation regions throughout the world.…”
Section: Introductionmentioning
confidence: 99%